Pyridoxal-5′-Phosphate Promotes Immunomodulatory Function of Adipose-Derived Mesenchymal Stem Cells through Indoleamine 2,3-Dioxygenase-1 and TLR4/NF-κB Pathway - Cong Li; Jinxian Huang; Huasu Zhu; Qing Shi; Dong Li; Xiuli Ju (Stem Cells International)
Adipose-derived mesenchymal stem cells (A-MSCs) are promising cellular therapies for the treatment of immune-mediated diseases. Non-gene editing technologies can improve the immune regulatory function of A-MSCs. Our preliminary experiments revealed that an active form of vitamin B6—pyridoxal-5′-phosphate (PLP)—plays an important role in regulating gene expression and cytokine secretion in A-MSCs in vivo. To further clarify the effect of PLP on receptors and cytokines related to the immune regulatory function of A-MSCs, a series of experiments were designed to verify the relationships between PLP and A-MSCs in vitro. Initially, A-MSCs were obtained, and cytokine secretion and the expression of IDO1, NF-κB, and Toll-like receptors in PLP-stimulated A-MSCs were evaluated. In addition, coculture was used to detect A-MSCs-mediated apoptosis of CD3+CD8+ T lymphocytes. These results showed that A-MSCs stimulated with PLP were highly proliferative, consistent with their pluripotent capacity. Further, the surface receptors TLR3, TLR4, IDO1, and NF-κB were upregulated, while TLR6 was downregulated. Concurrently, A-MSCs preconditioned with PLP had the greatest inhibitory effect on CD3+CD8+ T lymphocyte proliferation, indicating that PLP altered the immune regulatory function of A-MSCs through the regulation of TLRs and IDO1 expression.